Cost competitive steel fibre reinforced self-compacting concrete for structural applications - Barros, Joaquim A. O. (2009)
The present work resumes the research carried out to develop a cost competitive Steel Fibre Reinforced Self-Compacting Concrete (SFRSCC) for structural applications, such is the case of lightweight panels for building facades. A mix design method was developed taking into account the influence that fibres introduce in the skeleton phase of the composition. The concrete precast industry is one of the most suited industries for the use of SFRSCC, due to the possibility of assuring high levels of quality control from the mix composition phase up to the curing process of the manufactured structural elements. Since demoulding of the precast elements should be executed as earliest as possible, due to economic and stock management reasons, the influence of age on the SFRSCC mechanical properties was assessed carrying out compression and flexural tests. Compression and monotonic cyclic tests were also carried out to assess the predictive performance of analytical formulations. To appraise the structural possibilities of the developed SFRSCC, panel prototypes were subject to flexural and punching load configurations. The obtained results showed the great benefits provided by the fibre reinforcement mechanisms. Finally, a real scale panel was constructed and tested in an industrial environment, in order to help in the establishment of the best practices of technology transfer from laboratory to factory, as well as to determine the load carrying capacity of this type of structural elements.